The problem of sects - Willnatis, Arnoldas (Socialinė teorija, empirija, politika ir praktika, 2003)
The sects produce social problems in contemporary societies. The members of sects or new religious movements lose their personality, wealth and sometimes are pushed towards suicide. The state has to deal with these new religious movements in order to have healthier society. But there are some problems. First, it is a problem to define such a bad new religious movement. It will be time consuming process, because of dogmatic argument. The second problem is to choose the right means to deal with the movements. The goal of the paper is to present usable definition of the movement. Each organization can be evaluated by the criteria of humanity. The organization or movement is defined as a bad new religious movement or sect, if there is no humanity. Seven blocks of questions are presented in order to evaluate certain organization or movement.